Religion, the supernatural, and visual culture in early modern Europe: an album amicorum for Charles Zika - Spinks, Jennifer; Eichberger, Dagmar (Brill, 2015)
Preliminary Material -- Introduction: Scholarship, Friendship and Border-Crossing -- 1 The Collaboration from Hell: A Plague Strike Force at S. Pietro in Vincoli, Rome /Louise Marshall -- 2 The Demonic Possession of Richard Dugdale /Brian P. Levack -- 3 Salem Girls (1692): Problems of Gender and Agency /E. J. Kent -- 4 “Ringing of the Bells by Four White Spirits”: Two Seventeenth-Century English Earwitness Accounts of the Supernatural in Print Culture /Dolly MacKinnon -- 5 “It is a Great Disgrace for Our City”: Archbishop Antoninus and Heresy in Renaissance Florence /Peter Howard -- 6 Endor and Amsterdam: The Image of Witchcraft as a Weapon in the Political Arena /Hans de Waardt -- 7 Deep Down in Spirituality: Efforts of Seventeenth-Century New Netherlanders to Access God /Donna Merwick -- 8 Paraluther: Explaining an Unexpected Portrait of Paracelsus in Andreas Hartmann’s Curriculum Vitae Lutheri (1601) /Leigh T. I. Penman -- 9 “Making Feast of the Prisoner”: Roger Barlow, Hans Staden and Ideas of New World Cannibalism /Heather Dalton -- 10 Signs that Speak: Reporting the 1556 Comet across French and German Borders /Jennifer Spinks -- 11 Disorder in the Natural World: The Perspectives of the Sixteenth-Century Provincial Convent /Susan Broomhall -- 12 De Profundis: Linear Leviathans in the Lowlands /Larry Silver -- 13 The Ferocious Dragon and the Docile Elephant: The Unleashing of Sin in Rembrandt’s Garden of Eden /Shelley Perlove -- 14 Salience and the Snail: Liminality and Incarnation in Francesco del Cossa’s Annunciation (c. 1470) /Patricia Simons -- 15 Luther Relics /Lyndal Roper -- 16 The Art of Making Memory: Epitaphs, Tables and Adages at Westminster Abbey /Peter Sherlock -- 17 The Pope’s Merchandise and the Jesuits’ Trumpery: Catholic Relics and Protestant Polemic in Post-Reformation England /Alexandra Walsham -- Index of Names and Places.
Includes bibliographical references and index
Keywords: Europe; Electronic books; Festschrift; Aufsatzsammlung; Geschichte 1450-1700; Religiöse Kunst; Kultur; Das Übernatürliche; Das Übersinnliche; Religion; Europa